PENGARUH CORE SELF EVALUATIONS PADA KINERJA AUDITOR BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA PERWAKILAN PROVINSI BALI - Damayanti, Ni Nyoman Sri Rahayu; Wirakusuma, Made Gede; Wirama, Dewa Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2015)
Auditor performance have an important role in every audit assignment, one of them is to detect if there are irregularities that occurred in government financial statements which is capable of harming the State and society. BPK’s auditor performance becomes important to note considering the role of BPK as an institution that helped bring the State free from Corruption, Collusion and Nepotism. Core Self Evaluations as a personality model can be used to determine an individual performance. Various studies have previously shown that locus of control, emotional stability, self-esteem, and self-efficacy had an effect on individual performance (Judge and Bono, 2001, Erez and Judge, 2001, Bono and Judge, 2003). The sample selected by purposive sampling method and there are 43 auditors that accordance with the criteria. The result showed that locus of control, emotional stability, self-esteem, and self-efficacy had positive effect on auditor performance.
Keywords: Kinerja Auditor; Core Self Evaluations; BPK RI Perwakilan Provinsi Bali